INTERAÇÃO DA VIA DE SINALIZAÇÃO ROBO/SLIT NA CO-INFECÇÃO COM HPV EM TUMORES PENIANOS E SUA CORRELAÇÃO COM A CARCINOGÊNESE - SANTOS, Maria de Lourdes Figueiredo dos (2022)
Introduction: Penile cancer (CP) is a rare malignancy in developed countries occurring most frequently in men aged over 60. Among other risk factors, infection with human papillomavirus (HPV) should be highlighted. Recently, efforts have been undertaken to understand which signaling pathways are deregulated in CP. Among signaling pathways involved in cell differentiation and cancer there is the one mediated by the transmembrane Roundabout (ROBO) receptor and its cognate ligands, the SLIT proteins, suggested to correlate with tumor aggressiveness in multiple types of cancer. Objective: to analyze the expression of SLIT/ROBO genes in CP and their association with HPV DNA status and clinico-pathological variables. Methods: The study adopted a transversal, quantitative approach with 75 CP samples and matched adjacent tissue samples from the Maranhão Tumor and DNA Biobank (BTMA). Sociodemographic, clinical and pathological data were retrieved from medical records. Histological subtypes were determined on hematoxylin and eosin-stained slides. Genomic DNA was isolated and used for nested PCR for HPV DNA detection. HPV types wwre determined using the Anyplex II kit. Total RNA was isolated, converted into complementary DNA (cDNA) and the expression levels of SLIT2, SLIT3, ROBO1, ROBO2 and ROBO4 were studied using real-time quantitative PCR. Results: A majority of patients (52%) earned les than the minimum wage, had incomplete fundamental education (30,59%) self-identified as married (43,53%), and lived in inner Maranhão state locations (61,76%). The condylomatous (50%) and usual (25%) histological subtypes were most prevalent. All patients presented with squamous cell carcinoma, mostly on T2 and T3 stages. 61,84% were positive for HPV DNA and HPV types 11 and 16 were most frequently identified. 60% of patients showed infections with multiple HPV types. The presence of HPV were positively correlated with daily hygiene practice and absence of lymphovascular invasion. CP samples and matched adjacent samples showed identical expression levels of all genes. HPV DNA status was not associated with differential gene expression among tumor samples. There was a significant association between reduced SLIT2 expression levels and the presence of perineural invasion (p = 0,028) as well as between higher ROBO4 levels and the presence of lymphovascular invasion (p = 0,0303). Conclusion: CP remains strongly associated with HPV infection and it is necessary to clarify the role of "low-risk" viral types such as HPV11. The SLIT/ROBO pathway does not seem to be significantly modified by penile carcinogenesis, either via HPV-related or HPV-independent pathways. SLIT2 and ROBO4 expression levels were correlated with the tumor's biological behavior, suggesting their potential use as prognostic biomarkers.